2010
DOI: 10.1530/eje-10-0312
|View full text |Cite
|
Sign up to set email alerts
|

TSH and free thyroxine concentrations are associated with differing metabolic markers in euthyroid subjects

Abstract: Objective: To examine the association between thyroid function and the components of the metabolic syndrome and insulin resistance in an Hispanic population. Design: Cross-sectional study. Methods: Subjects with no history of thyroid disease or diabetes were included. Thyroid function was stratified as euthyroid or subclinical hypothyroidism (SCH) status and subsequently by free thyroxine (FT 4 ) and TSH tertiles. The association of the metabolic syndrome components (defined by 2004 Adult Treatment Panel III c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
194
7
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(233 citation statements)
references
References 23 publications
20
194
7
7
Order By: Relevance
“…SCH subjects have been shown to have similar (13), higher (7,8), or lower (12) insulin and HOMA-IR levels, compared with euthyroid control subjects. Similarly, Garduño-Garcia et al (13) found that the prevalence of MS was not different between SCH subjects and individuals with normal thyroid function, while another study demonstrated that the syndrome was significantly more prevalent in subjects with both overt thyroid failure and SCH than in euthyroid subjects (9). Interestingly, a very recent study conducted in overweight and obese children has demonstrated a multivariate-adjusted association of SCH with insulin resistance and MS (7).…”
Section: European Journal Of Endocrinologymentioning
confidence: 95%
See 1 more Smart Citation
“…SCH subjects have been shown to have similar (13), higher (7,8), or lower (12) insulin and HOMA-IR levels, compared with euthyroid control subjects. Similarly, Garduño-Garcia et al (13) found that the prevalence of MS was not different between SCH subjects and individuals with normal thyroid function, while another study demonstrated that the syndrome was significantly more prevalent in subjects with both overt thyroid failure and SCH than in euthyroid subjects (9). Interestingly, a very recent study conducted in overweight and obese children has demonstrated a multivariate-adjusted association of SCH with insulin resistance and MS (7).…”
Section: European Journal Of Endocrinologymentioning
confidence: 95%
“…Although some studies have reported associations of SCH with insulin resistance (7,8), metabolic syndrome (MS) (7,9), and CHD (10,11), not all previous findings have been consistent (12,13,14). Recent studies in adults (9,15,16) and children (7) have shown that SCH is closely associated with NAFLD independent of potential confounders.…”
mentioning
confidence: 99%
“…Garduño-Garcia and cols. reported a significant association between fT4 levels and high-density lipoprotein cholesterol, insulin and HOMA-IR (10).…”
Section: Introductionmentioning
confidence: 96%
“…The association between serum TSH and the components of metabolic syndrome varied in different studies. In some recent studies, thyroid dysfunction (23) and even TSH within the normal range (19,24,25) were reported to be associated with insulin resistance and components of metabolic syndrome. By contrast, some other studies failed to detect a significant association between TSH and insulin resistance (19,21,22,26).…”
Section: Discussionmentioning
confidence: 99%